Students’ Voices on the Implementation of Visual Text Analysis Approach in Critical Reading Class - Lailatus Sa’adah; Masriatus Sholikhah (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2018)
This research was conducted on investigating students’ perception on how the implementation of visual text analysis approach elevate their critical thinking and drawing the strengths and the weaknesses of this approach in critical reading class for EFL college Students. To convince those two research goals, descriptive qualitative approach with document analysis technique was implemented. Series of document obtained from interview and questionnaire. In addition, during the class, the students were given materials dealing with types and functions of logical fallacy (bandwagon, ad hominem, red herring, straw man, genetic fallacy, appeal to believe, and appeal of authority) which implemented in authentic texts (memes, posters, and comic strips) retrieved from social media (Facebook and Instagram). The result showed that the implementation of VTA approach is beneficial and fruitful in escalating students’ critical thinking, further it was also joyful to have such kind of class for they have a better insight of how to interpret a text beyond the textual feature. In addition, the VTA approach combined with content of logical fallacy also contributed a great deal of logical reasoning understanding which deliver to avoiding and minimizing them easily vulnerable from viral hoaxes mainly in the SARA issues.